2015
DOI: 10.3201/eid2111.150813
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Primary Multidrug-Resistant Tuberculosis, Vladimir Region, Russia

Abstract: We studied the epidemiology of drug-resistant tuberculosis (TB) in Vladimir Region, Russia, in 2012. Most cases of multidrug-resistant TB (MDR TB) were caused by transmission of drug-resistant strains, and >33% were in patients referred for testing after mass radiographic screening. Early diagnosis of drug resistance is essential for preventing transmission of MDR TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Our finding was comparable to the results of similar surveys conducted in Ethiopia, 13 China, 14 and Brazil. 15 However, it was lower than studies conducted across the globe, such as Ethiopia (26.9%), 16 South Africa (49%), 17 the eastern coast of China (53.9), 2 Vladimir Region of Russia (73.3%), 18 and reports in a review of data for 30 countries having anti-tuberculosis drug resistance surveillance (31%-82%). 19 This can be due to these countries taking the lion share of the global DR-TB patients and correspondingly increasing the prevalence of a primary form of RR/MDR-TB through increased transmission.…”
Section: Discussionmentioning
confidence: 83%
“…Our finding was comparable to the results of similar surveys conducted in Ethiopia, 13 China, 14 and Brazil. 15 However, it was lower than studies conducted across the globe, such as Ethiopia (26.9%), 16 South Africa (49%), 17 the eastern coast of China (53.9), 2 Vladimir Region of Russia (73.3%), 18 and reports in a review of data for 30 countries having anti-tuberculosis drug resistance surveillance (31%-82%). 19 This can be due to these countries taking the lion share of the global DR-TB patients and correspondingly increasing the prevalence of a primary form of RR/MDR-TB through increased transmission.…”
Section: Discussionmentioning
confidence: 83%
“…Using prospective cohort design, we assessed impact of Xpert on treatment initiation and outcomes of RIF-resistant and RIF-susceptible TB patients in Vladimir Regional TB Dispensary (the Dispensary), Russia. The Dispensary is a referral center for TB patients in Vladimir region and serves about 25% of all TB patients in the region [ 10 ]. The patients were referred to the Dispensary as presumptive TB patients after visiting primary health care physician or pulmonologist based on symptoms or results of mass TB screening.…”
Section: Methodsmentioning
confidence: 99%
“…Ershova et al observed in their research that out of 60 MDR-TB patients 44 patients were newly diagnosed patients with no previous history of taking anti-TB drugs, which was near about 73 percent of the cohort. 12 This is a clear-cut sign of escalating trends of primary acquired MDR-TB in the community, which is alarming for policy makers.…”
Section: Discussionmentioning
confidence: 99%